Novel ollusvirus detected in a solitary wild bee species (Osmia taurus) in Japan - Takemae, Hitoshi; Nunomura, Yuka; Yokota, Tomoko; Oba, Mami; Mizutani, Tetsuya; Hsu, Wei-Li; Sakamoto, Yoshiko (Archives of virology, 2023)
Pathogens of wild bees in Japan remain largely unknown. We examined viruses harbored by solitary wild Osmia bees, including Osmia cornifrons and Osmia taurus . Interestingly, the full-length genome of a novel virus (designated as "Osmia-associated bee chuvirus", OABV) was identified in three Osmia taurus bees collected in Fukushima prefecture. The sequences and genomic features are similar to those of Scaldis River bee virus. Phylogenetic analysis based on RNA-dependent RNA polymerase, glycoprotein, and nucleoprotein sequences showed that OABV formed a subcluster within ollusviruses and was closely related to strains identified in European countries. This study extends our knowledge of wild bee parasites in Japan.